Rear seatbelt policy in Malaysia and the United Kingdom (UK): an endeavour of mitigating the gap / Mohd Rozaimy Ridzuan and Noor Amira Syazwani Abd. Rahman - Ridzuan, Mohd Rozaimy; Abd. Rahman, Noor Amira Syazwani (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Most developing countries are facing high rates of road fatality. This also occurs in Malaysia and the number of road fatalities and severe injuries caused by road accidents can be effectively reduced using the rear seat belt. There is an urgent need to reduce the road fatality rate as this issue offers several drawbacks to the country as well as to individuals in terms of economy, human capital, and loss of family members. The aim of this paper is to delineate the similarities and differences between Malaysia and United Kingdom (UK)'s rear seat belt policy. Methodologically, an extensive literature review was carried out by the researchers based on the policies formulated in Malaysia and UK. A content analysis was also performed to identify major themes and draw a comparison between the rear seat belt policies in these two countries. This paper concludes that in Malaysia, there are no regulations that can reduce the amount of insurance claim if the passengers were found not wearing rear seat belts in cases of road accidents. Meanwhile, in UK, the claim for insurance can be reduced by 15-50 percent (%) if the passengers were found to have not worn rear seat belts in cases of road. Besides that, in Malaysia, it is not compulsory for passengers to wear seat belts in buses, minibuses, and coaches. However, in the UK, the wearing of seat belts in the buses, minibuses, and coaches is compulsory. In order to effectively reduce the road fatality rate in Malaysia, it is suggested that the government to emulate the best practices made by the UK government in reducing its number of road fatalities, which is by making it compulsory for passengers of the buses and coaches to wear seat belts.